2019
DOI: 10.46743/2160-3715/2019.3603
|View full text |Cite
|
Sign up to set email alerts
|

Choose Your Words Wisely: Descriptions of a Professional Early Childhood Practitioner

Abstract: The purpose of this study was to understand the components that determine quality early childhood education and Care (ECEC) from the views of practitioners and parents participating in the ECCE Scheme (2010). A major component of quality ECCE as identified by practitioners in this study related to professionalism in ECEC. This paper presents a critical view on traditional perspectives on what it means to be a professional within the context of ECCE. It seems that within the ECCE model, a professional practitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…As it becomes evident, both from our results and previous research (Harwood et al, 2013;Oke et al, 2019) an ethic of care prevails in infant classrooms both in terms of educators' professionalism and in terms of the role and aims of an educator towards infants. On the other hand, in toddler classrooms educative aspects and aims, as well as attention to children's independence and autonomy are gaining increased attention.…”
Section: The Role and Occupational Activities Of Infant-toddler Educa...supporting
confidence: 71%
See 1 more Smart Citation
“…As it becomes evident, both from our results and previous research (Harwood et al, 2013;Oke et al, 2019) an ethic of care prevails in infant classrooms both in terms of educators' professionalism and in terms of the role and aims of an educator towards infants. On the other hand, in toddler classrooms educative aspects and aims, as well as attention to children's independence and autonomy are gaining increased attention.…”
Section: The Role and Occupational Activities Of Infant-toddler Educa...supporting
confidence: 71%
“…On the other hand, our results are in line with the results of the study conducted by Harwood et al (2013) who also found that participants emphasize their love for their work as well as their love for children as essential qualities. Oke et al (2019) also found that educators prioritize and emphasize interpersonal skills (e.g. patient, caring, creative, etc.)…”
Section: Attributes Of a Professional Infant-toddler Educatormentioning
confidence: 94%
“…The objectives and criteria required to participate were detailed Source. Adapted from Morrow and Smith (1995), Strauss and Corbin (1990), and Oke et al (2019). in a one-page information sheet using language free of jargon.…”
Section: Ethical Considerationsmentioning
confidence: 99%